Optimal Rules bagi Instrumen Kebijakan Moneter di Indonesia: Pengujian Empiris Model Guender - Adnin, Zenathan; Mardanugraha, Eugenia (UI Scholars Hub, 2008)
This study aims to test model developed by Guender (2002) in determining optimal rules for monetary policy instrument in Indonesia. The test is conducted by estimating parameters of IS equation and Forward Looking Phillips Curve. The result expected is rules for determining the optimal interest rate which is influenced by the gap between actual and targeted inflation. The result shows that in the era of inflation targeting the interest rate setting policy as monetary policy instrument has focus on output stability rather than inflation stability. Finally, the study concludes that the interest rate targeting as BI rate has not being optimal.